A comparative study of spray-dried medicinal plant aqueous extracts: Drying performance and product quality - Gallo, Loreana Carolina (2015)
In the manufacture of herbal medicinal tablets, dried plant extracts are employed as the therapeutic ingredient. These powders, usually obtained by spray drying, are typically hygroscopic and possess poor flow and compactability for the manufacture of tablets by direct compression (DC). Besides, spray-drying operating conditions and liquid feed composition are reported to be dependent on the herbal medicine. Consequently, the production of dried extractsimplies long new product development times. Therefore, the goal of this paper was to: a) provide recommendations as initial production point of herbal powders suitable for DC by spray drying and b) study the powder properties to identify those that are affected by the extract nature. Particularly, a unique set of operating conditions was found to be appropriate to produce powders of seven different medicinal plant extracts. In fact, all the spray-dried products showed adequate flowability, stability and compactability.Powders properties, as particle size and morphology, moisture content, hygroscopicity, flowability and compact hardness were not a function of the type of herb. Conversely, the process yields and glass transition temperature, particle and bulk densities, powder composition, compact porosity, wetting and disintegration times were found to be dependent on the chemical nature of the herbs.